Improvement of DSIM control using fuzzy third-order sliding mode approach optimized by MOA - Belkaid, Rahma; Youb, Lamia; Naceri, Farid; Boukhalfa, Ghoulem Allah (International Journal of Power Electronics and Drive Systems (IJPEDS), 2025)
This study focuses on the contribution of a new hybrid controller based on the sliding mode technique associated with fuzzy logic and optimized by an innovative approach called the mayfly optimization algorithm (MOA) to improve the drive of the dual star induction motor (DSIM). The performance and robustness of this system are analyzed under different operating conditions with three proposed strategies and compared with each other under the MATLAB/Simulink environment. Through the simulation results obtained, we realize that the method that integrates the MOA with a hybrid controller associating the third order sliding mode with fuzzy logic (MOA-FTOSMC) makes a significant contribution to research work in this field and offers the best dynamic performance and adequately manages the uncertainty and variation of the system parameters under different operating regimes.